Irrigation Water Availability for Oil Palm Cultivation in Areas Affected by Shifting Cultivation in Arunachal Pradesh - Roy, Pankaj Kumar; Kar, Amlanjyoti; Ray, Chandan; Mazumdar, Asis (Indian Forester, 2010)
Shifting cultivation provided a way of life for most of the ethnic groups of north eastern states. Policy approach to deal with shifting cultivation in Arunachal Pradesh aims to replacing it with permanent forms ofland use by cultivation of oil palm as per availability and suitability of land. In Jhum land area oil palm plantation may be promising in the state. However, as per the requirement of climatic factors and availability of irrigation water, the oil palm cultivation could be practiced in areas where a compact area between 450-500 hectares of land and sufficient rainfall and SUlllly days are available. Since, the minimum land requirement for oil palm plantation, advocated by NRCOp, is 500 ha, a total number of nearly 60,000 nos. plant may be grown in such a composite oil palm garden. In view of non availability of a considerable land area of 500 hectares under single holding and cost involvement, community participation should be encouraged. Since irrigation water requirement of each plant is 200 litres per day, total quantity of 12 million litres or 0.012 MCM of water per day would be required for sustainable growth of such oil palm plantation. Various practices of watershed development can also be applied in the sloping terrain. In the foothill areas of Arunachal Pradesh, with optimum minimum temperature of 6-10Â°C, shallow aquifers may be tapped with shallow tube wells or dug wells/collector wells with infiltration galleries. Surface water/rain water resources could be developed in and around Jhum cultivation areas through construction of check dams in series with sub surface dams and through construction of ponds.